THE ROLE AND PRINCIPLES OF ORGANIZING INDEPENDENT WORK OF STUDENTS AS ONE OF THE CRUSHING TASKS OF MODERN EDUCATION (Web of Teachers: Inderscience Research, 2025)
The article emphasizes the relevance of research in the field of pedagogy and teaching methods, with special attention paid to modern and interactive methods of education in the context of globalization and technological progress. The role of higher education institutions in organizing an effective educational process using innovative technologies and new methods is considered. The importance of independent work of students as a means of forming professional training and developing personal qualities is highlighted.